Association between body weight perception and intuitive eating among undergraduate students in China: the mediating role of body image - Zhu, Yuanyuan; Gao, Jiage; Gao, Qinyi; Chen, Dandan; Zeng, Zhi (Frontiers in Nutrition, 2024)
Background The association between body weight perception and intuitive eating among undergraduate students in China remains insufficiently understood. In the present study, we were aimed to examine the correlation between body weight perception, body image, and intuitive eating and determine whether the link between body weight perception and intuitive eating was influenced by body image. Methods A total of 1,050 undergraduate students completed the survey. Participants provided self-reported demographic details and completed two structured scales. The Body Esteem Scale for Adolescents and Adults (BESAA) and the Intuitive Eating Scale-2 (IES-2) were employed to assess body image and intuitive eating. Analysis of the mediation model was conducted using version 4.1 of the PROCESS Macro. Results with a value of p less than 0.05 were deemed statistically significant. Results The average age of the participants was 20.08 years (SD = 1.64). Among the students, 837 (79.7%) were female, and 212 (20.3%) were male. Body image (r = −0.429, p < 0.001) and intuitive eating (r = −0.313, p < 0.001) exhibited significant negative associations with body weight perception. Furthermore, body image showed a significant positive correlation with intuitive eating (r = 0.318, p < 0.001). Significant mediating effects of body image were identified concerning intuitive eating and body weight perception in the right weight (95% bootstrap CI = 0.007, 0.040) and overweight groups (95% bootstrap CI = −0.048, −0.009). The indirect effects of body image constituted 12.19% and 15.33% of the total effects of intuitive eating in these two groups. Conclusion Although the indirect effects were not substantial, these outcomes shed light on the partial understanding of how body weight perception impacted intuitive eating via body image. Importantly, our findings emphasized the significance of body image and body weight perception, offering a novel insight for prospective interventions targeting undergraduate students.